THE INFLUENCE OF PRINCIPAL'S TRANSFORMATIONAL LEADERSHIP STYLE, SCHOOL CULTURE, AND TEACHER PROFESSIONALISM ON LEARNING QUALITY IN JUNIOR HIGH SCHOOL - Wita Setiyanti; Widya Kusumaningsih; Nurkolis Nurkolis (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
The quality of learning in schools is shaped by several key factors, including the principal's leadership style, school culture, and teacher professionalism. This research aims to examine the individual and combined effects of these factors on the learning quality in public junior high schools in the Kendal region. Using a quantitative approach, the study collected data from 118 respondents across 4 schools through observations and questionnaires. The findings indicate that (1) transformational leadership significantly influences the quality of learning, accounting for 73.3% of its variation. (2) School culture also plays a crucial role, explaining 68.9% of the variation in learning quality. (3) Teacher professionalism is another important factor, contributing 73.0% to the variation in learning outcomes. (4) When combined, transformational leadership, school culture, and teacher professionalism together account for 78.7% of the variation in learning quality. To improve learning outcomes, it is recommended that school principals focus on developing a transformational leadership style through ongoing training. Additionally, schools should actively nurture a positive and strong culture by engaging the entire educational community, including teachers, students, and parents. Teachers are encouraged to enhance their professionalism through structured training, continuous personal development, and fostering a high level of commitment to their teaching responsibilities.